IMPACT OF DIGITAL MATURITY ON FINANCIAL PERFORMANCE: PRE AND DURING PANDEMIC IN INDONESIA - Kurniawan Winata, Robbie
The advancement of information technology has been changing societal evolution and how people live. The concept of digitalization has also changed from being a small and future idea to a revolutionary reality concept. This research aims to present studies related to digital maturity and highlight its impact on financial performance while also applying methodologies from recent research across various fields. In this research, we used a quantitative method with panel data regression. The samples were taken from Indonesian LQ45 companies from 2018-2022. Four models have been developed based on variables that measure profitability, sales expansion, and stock return to analyze the impact of digital maturity. Based on the models that have been developed, the digital maturity of a company has an effect on company performance at different levels. Return on asset and stock return models show that digital maturity improves company performance. On the other hand, two other models show digital maturity has little to no contributions toward company performance, which is measured by its net profit margin and sales growth. Since digital maturity increases operational efficiency, lowers costs, and broadens market reach, it is critical for boosting key performance measures including Return on Assets (ROA), sales growth, and stock return. Its effect on Net Profit Margin (NPM), however, is less noticeable because pricing tactics and immediate cost structures have a greater influence on NPM than does digital capabilities. The short-term impacts of digital maturity on profit margins may be constrained by the high upfront costs of digital expenditures and ongoing competitive challenges. In the future, companies need to implement digitalization in their company to improve their financial performance, and shareholders should consider applying digitalization even after the pandemic ends.